Mechanism-based population pharmacokinetic and pharmacodynamic modeling of intravenous and intranasal dexmedetomidine in healthy subjects - Yoo, Heedoo; Iirola, Timo; Vilo, Sanna; Manner, Tuula; Aantaa, Riku; Lahtinen, Maria; Scheinin, Mika; Olkkola, Klaus T.; Jusko, William J. (European journal of clinical pharmacology, 2015)
Purpose Dexmedetomidine is an α 2 -adrenoceptor agonist used for perioperative and intensive care sedation. This study develops mechanism-based population pharmacokinetic-pharmacodynamic models for the cardiovascular and central nervous system (CNS) effects of intravenously (IV) and intranasally (IN) administered dexmedetomidine in healthy subjects. Method Single doses of 84 μg of dexmedetomidine were given once IV and once IN to six healthy men. Plasma dexmedetomidine concentrations were measured for 10 h along with plasma concentrations of norepinephrine (NE) and epinephrine (E). Blood pressure, heart rate, and CNS drug effects (three visual analog scales and bispectral index) were monitored to assess the pharmacological effects of dexmedetomidine. PK-PD modeling was performed for recently published data (Eur J Clin Pharmacol 67: 825, 2011). Results Pharmacokinetic profiles for both IV and IN doses of dexmedetomidine were well fitted using a two-compartment PK model. Intranasal bioavailability was 82 %. Dexmedetomidine inhibited the release of NE and E to induce their decline in blood. This decrease in NE was captured with an indirect response model. The concentrations of the mediator NE served via a biophase/transduction step and nonlinear pharmacologic functions to produce reductions in blood pressure and heart rate, while a direct effect model was used for the CNS effects. Conclusion The comprehensive panel of two biomarkers and seven response measures were well captured by the population PK/PD models. The subjects were more sensitive to the CNS (lower EC 50 values) than cardiovascular effects of dexmedetomidine.